2006
DOI: 10.1063/1.2184431
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the lowest excitonic transition for an InAs ultrathin quantum well

Abstract: Temperature dependent photoluminescence and photoreflectance techniques are used to investigate the lowest excitonic transition of InAs ultrathin quantum well. It is shown that the temperature dependence of the lowest energy transition follows the band gap variation of GaAs barrier, which is well reproduced by calculated results based on the envelope function approximation with significant corrections due to strain and temperature dependences of the confinement potential. A redshift in photoluminescence peak e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…In such cases, SPS becomes a potentially useful tool since it can measure essentially very small values of the absorption coefficient such as in the case of InAs QDs [19][20][21][22] or even ultrathin InAs QWs. 23 This was the main reason we also applied the complementary SPS technique to the InAs/InGaAs/InP QD sample and indeed found a measurable signal at all temperatures. Figure 6 shows representative SPS spectra at three selected temperatures, showing that the overall magnitude of the SPS signal first increases between ϳ9 and ϳ100 K but then subsequently drops.…”
Section: Resultsmentioning
confidence: 89%
“…In such cases, SPS becomes a potentially useful tool since it can measure essentially very small values of the absorption coefficient such as in the case of InAs QDs [19][20][21][22] or even ultrathin InAs QWs. 23 This was the main reason we also applied the complementary SPS technique to the InAs/InGaAs/InP QD sample and indeed found a measurable signal at all temperatures. Figure 6 shows representative SPS spectra at three selected temperatures, showing that the overall magnitude of the SPS signal first increases between ϳ9 and ϳ100 K but then subsequently drops.…”
Section: Resultsmentioning
confidence: 89%
“…6 where we present the SPS spectrum for an InAs ultrathin QW. Thickness of this QW is kept very low (3.6 Å ) such that no relaxation is seen in HRXRD measurement and an estimate of QW thickness can easily be obtained from the simulation of HRXRD data [8]. We did not observe any PL signal above 120 K for this sample.…”
Section: Methodsmentioning
confidence: 84%
“…Therefore, it is confirmed that the transition seen at 1.36 eV is related to the InAs/GaAs ultrathin QW only. From quantum mechanical calculations [8], we identify this as e 1 -hh 1 transition. Features A, Q and B are reported earlier and are related to semi-insulating GaAs substrates [6,9].…”
Section: Resultsmentioning
confidence: 99%
“…7 Ultrathin quantum wells (QWs) with typical thickness of 1-2 monolayer (ML) have been also studied due to their unique electronic and optical properties leading to their use in the optoelectronic devices. 8,9 The issue of type-II band alignment for InP/GaAs heterostructure has been addressed by several groups, where it is understood that the electrons (holes) are confined in the conduction (valance) band of InP (GaAs) respectively. 1,7,10-12 There exist several reports dealing with the optical properties of InP/GaAs type-II quantum dots (QDs), where signature of InP/GaAs ultrathin QW, known as wetting layer in the QD structures, has been observed in the low temperature photoluminescence (PL) spectra.…”
Section: Structural Optical and Electrical Properties Of Movpe Grownmentioning
confidence: 99%